2009
DOI: 10.1177/1534735409355293
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Disruption, Fatigue, and Anorexia Clustering in Advanced Cancer Patients: Implications for Innovative Therapeutic Approaches

Abstract: A disruption of the circadian timing system, as identified by monitoring of marker biorhythms, is common in cancer patients. The recording of the rest-activity rhythm with a wrist actigraph has been commonly used. This noninvasive monitoring allows a robust estimation of circadian disruption. The authors have previously found that altered patterns of circadian rest-activity rhythms are significantly and independently associated with the severity of fatigue and anorexia in patients with metastatic colorectal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 99 publications
8
56
0
Order By: Relevance
“…Our subgroup analyses furthermore substantiate the hypothesis that excessive toxicity could hamper the efficacy of circadian-based chronomodulated chemotherapy 8,30,32,33,35,36 . In this study, we found that the complaint of sleep troubles at the last ontreatment assessment was correlated with shorter overall survival in patients treated with chronoFLO4, but not on FOLFOX2.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Our subgroup analyses furthermore substantiate the hypothesis that excessive toxicity could hamper the efficacy of circadian-based chronomodulated chemotherapy 8,30,32,33,35,36 . In this study, we found that the complaint of sleep troubles at the last ontreatment assessment was correlated with shorter overall survival in patients treated with chronoFLO4, but not on FOLFOX2.…”
Section: Discussionsupporting
confidence: 73%
“…Thus, our findings underscore the hypothesis that optimal efficacy of circadian-based chronotherapy is associated with optimal tolerability 32,33,37 . Indeed, the persistence of robust circadian function during chemotherapy, a recently documented phenomenon 38 , associated with lower incidence and/or severity of chemotherapy toxicity, has been shown to predict for better efficacy of chronotherapy 8,30,32,33,35,36 . Thus, as for severe neutropenia or clinically meaningful fatigue and/or weight loss, subjective sleep complaints during treatment might reflect disrupted circadian function, decreasing chronotherapy effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This measure is in fact associated with all four variables, which are under circadian control (Mormont et al, 2000, Innominato et al, Innominato et al, 2009aInnominato et al, 2009b). These common cancer-related problems may interact and reinforce one another (Spiegel, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A disruption of the circadian timing system, as identified by monitoring maker biorhythms, is common in cancer patients [44]. A body of evidence paves the path for innovative therapeutic approaches targeting the circadian timing system in an effort to diminish constitutional symptoms induced by cancer and some anticancer treatments.…”
Section: Cancermentioning
confidence: 99%